Contribution of the pst-phoU Operon to Cell Adherence by Atypical Enteropathogenic Escherichia coli and Virulence of Citrobacter rodentium - Cheng, Catherine (American Society for Microbiology (ASM), 2009)
Strains of enteropathogenic Escherichia coli (EPEC) generally employ the adhesins bundle-forming pili (Bfp) and intimin to colonize the intestine. Atypical EPEC strains possess intimin but are negative for Bfp and, yet, are able to cause disease. To identify alternative adhesins to Bfp in atypical EPEC, we constructed a transposon mutant library of atypical EPEC strain E128012 (serotype O114:H2) using TnphoA. Six mutants that had lost the ability to adhere to HEp-2 cells were identified, and in all six mutants TnphoA had inserted into the pstSCAB-phoU (Pst) operon. To determine if the Pst operon is required for adherence, we used site-directed mutagenesis to construct a pstCA mutant of E128012. The resultant mutant showed a reduced ability to adhere to HEp-2 cells and T84 intestinal epithelial cells, which was restored by trans-complementation with intact pstCA. To determine if pst contributes to bacterial colonization in vivo, a pstCA mutation was made in the EPEC-like murine pathogen, Citrobacter rodentium. C57BL/6 mice infected perorally with the pstCA mutant of C. rodentium excreted significantly lower numbers of C. rodentium than those given the wild-type strain. Moreover, colonic hyperplasia and diarrhea, which are features of infections with C. rodentium, were not observed in mice infected with the pstCA mutant but did occur in mice given the trans-complemented mutant. As mutations in pst genes generally lead to constitutive expression of the Pho regulon, our findings suggested that the Pho regulon may contribute to the reduced virulence of the pstCA mutants. To investigate this, we inactivated phoB in the pstCA mutants of EPEC E128012 and C. rodentium and found that the phoB mutation restored the adherent phenotype of both mutant strains. These results demonstrate that Pst contributes to the virulence of atypical EPEC and C. rodentium, probably by causing increased expression of an unidentified, Pho-regulated adhesin.